Membangun Kurikulum Sains Islami: Relevansi Al-Quran dan Hadis dalam Pendidikan STEM di Era Digital - Mei Rahmani (Arba: Jurnal Studi Keislaman, 2025)
In the digital era marked by the rapid development of technology and science, the STEM-based educational approach is a priority in the global education system, including in Indonesia. However, integrating Islamic values into the STEM curriculum remains a challenge. This raises concerns about the occurrence of a dichotomy between religious knowledge and science. Therefore, the development of an Islamic science curriculum is very important to bridge this gap and ensure that science education remains in line with the values ​​of the Qur’an and Hadith. This study aims to formulate the concept of an Islamic science curriculum that is relevant to the STEM approach and by the challenges of the digital age. The method used is a library research with a qualitative approach, analyzing literature related to Islamic education, STEM education, and the integration of science from the perspective of the Qur’an and Hadith. The results of the study demonstrate that the Qur’an and Hadith incorporate scientific principles aligned with STEM values, including observation, experimentation, scientific ethics, and environmental responsibility. This integration can form a curriculum framework that not only encourages scientific literacy but also strengthens the spiritual and ethical character of students. In conclusion, an Islamic science curriculum based on the Qur’an and Hadith can be a strong foundation in developing holistic and character-based STEM education in the digital era.